Influence of plant age on susceptibility of pigeonpea to Phytophthora blight - and V.K. SHEILA, NANDITA SARKAR*, Y.L. NENE, M.V. REDDY (Indian Phytopathology, 2002)
The influence of pigeonpea plant age on susceptibility to Phytophthora drechsleri f. sp. cajani was investigated in pot tests. Plant mortality decreased with increased plant age in most of the pigeonpca genotypes tested.